Lichen Simplex Chronicus That Accompanies Anogenital Warts during the Childhood - Özlem Seçilmiş Kerimoğlu; Nasuh Utku Doğan; Aybike Tazegül; Mehtap Karameşe; Hasan Beyhekim; Çetin Çelik (Case Reports in Medicine)
Anogenital warts and lichen simplex chronicus (LSC) are rarely seen during the childhood. A 9-year-old girl has been presented to hospital by her parents with itching in the anogenital area. There were anogenital warts and a different erythematous lesion in the perianal region. On the pulpa of the right thumb, there was a wart extending under the nail. The lesions are surgically removed. The results of the histopathological examination were reported as condyloma acuminata and LSC. Children with anogenital warts should be examined carefully to discover the transmission route and other possible concomitant cutaneous diseases.